Περί αλφαβητισμού, αιρέσεων, εικονογραφίας και πολιτικών φιλοδοξιών στα μολυβδόβουλλα του Νικηφόρου Βοτανειάτη (περίπου 1001/2-1081) - ΚΑΡΑΓΙΩΡΓΟΥ Όλγα (Byzantina Symmeikta, 2008)
ABOUT LITERACY, HERESY, ICONOGRAPHY AND POLITICAL AMBITION ON THE SEALS OF NIKEPHOROS BOTANEIATES The scarce information of the 11th-c. historians on the long military career of Nikephoros Botaneiates before his ascension to the throne is supplemented to a great extent by 31 lead seals of Botaneiates, today kept in private and museum collections in more than seven countries around the world. The epigraphic and iconographic study of this sigillographic material reconstructs the social ascent and military activities of the future emperor, while at the same time it sheds light on his personality (level of culture, religious sensitivities, political ambition) and the socio-political conditions of his era.